Sulapa Eppa: Bissu, Kosmologi Bugis, dan Politik Ekologi Queer - Feby Triadi; Petsy Jessy Ismoyo (Yayasan Jurnal Perempuan, 2022)
Various discourses about locality and indigenous peoples emerged as an effort to overcome the climate crisis. This term is also a part of seeing the sustainability of nature. This paper departs from arguments such as queer ecological studies and the indigenous paradigm. Furthermore, some of these academic studies are used to foster focus through indigenous knowledge in recalibrating the God-Human-Nature relationship through Bugis cosmology and the role of the Bissu. The main argument in this paper is to present Bugis knowledge and understand the embodied resistance in the existence of Bissu in South Sulawesi. This study used a qualitative method with participant observation and in-depth interviews. Data collection was carried out in two steps, namely, literature study, which was followed by participant observation and in-depth interviews. Data is then collected, classified, and interpreted through the indigenous paradigm as an effort to decolonize knowledge. The results of this study show some holistic, cyclic knowledge, and based on experience in the Bugis community, namely: (1) Environmental conservation can be guided by Sulapa Eppa as an environmental ethic based on Bugis cosmology; (2) Sangiang Serri as an eco-prophetic ritual that denounced heteropatriarchy; (3) Embodied resistance of Bissu’s gender identity ambivalence as a political representation of queer ecology.